Geotourism potential of underground sites in Costa Rica - Ulloa Carmiol, Andrés (2013)
Although tourism is presently the main source of income of the Republic of Costa Rica, making an analysis of the offer and demand of the topic of "underground sites as tourist attractions", it is evident that in our country this activity is minimal, with percentage figures that are not even taken into account in the statistics. At government level, there's only one National Park whose focus is caves (Barra Honda); in this aspect, there's also very little and ambiguous legislation. At a private enterprise level, there are only five karstic underground sites worthy of mention, of which only two can qualify as 'business operations'. The other 3 are underground sites to which occasionally and informal visits are launched, but it is still difficult to find references, even in the web.